Effects of bentonite slurry on the skin friction capacity of bored piles - Gravador, Anna Grace N. (2008)
Modified Direct Shear Tests were performed to study the skin friction capacity effects of using the bentonite slurry for drilling bored piles in saturated silty sands. Shear tests were done in four phases of experiments on four different types of interfaces: soil-soil interface, soil-concrete interface, soil-2mm thick bentonite-concrete interface and soil 2.5mm thick bentonite-concrete interface. Measurements of the bentonite slurry rheological properties were taken with time prior to the interface tests to understand the behavior of bentonite slurries and more aptly design the third and fourth phases of the direct shear tests. The interface friction parameters such as Φ, δ and β obtained from each experiment phase were then used to compute for the skin friction capacities for each type of interface. Bentonite slurry was found to decrease the skin friction by 17.90% and 18.15% if 2mm and 2.5mm mudcake thickness, respectively are formed between at the interface of the soil and concrete. The experiment results significantly show that the silty sand-concrete interface behaves like more of a clay-concrete interface when bentonite slurry with 2mm to 2.5mm mudcake thicknesses is present at the interface of the silty sand soil and concrete.
Thesis (M.S. Civil Engineering)--University of the Philippines, Diliman.
Keywords: Piling (Civil engineering).; Bentonite slurry; Shear strength of soils -- Testing